Pluralism and Interreligious Dialogue: An Islamic Perspective on Socio-Religious Relations - Muttaqo, Moh. Ali; Anwar, Khairil (EDUMALSYS Journal of Research in Education Management, 2025)
Religious diversity is an unavoidable social reality. However, this diversity often leads to tension and conflict between religious communities. The concept of pluralism comes as a solution to create a harmonious life by emphasizing mutual respect and understanding of differences. This research aims to examine the Islamic perspective in building harmonious socio-religious relations in the midst of pluralism by using the literature study method, this research analyzes the concept of pluralism and interfaith dialogue in the Islamic perspective through a qualitative approach. The data used comes from various academic literatures, including books, scientific journals, and relevant official documents. The results show that the concept of Tri Kerukunan (internal religious harmony, inter-religious harmony, and harmony between religious communities and the government) is the main asset in building harmonious religious pluralism in Indonesia. In addition, social dynamics in religious pluralism in contemporary society face various challenges, such as differences in theological views and the spread of information that can worsen inter-religious relations. Therefore, the active involvement of various parties, including religious leaders and the government, is needed to manage more inclusive social interactions and build a civilized society.